EVALUATION OF ANTI-ALZHEIMER ACTIVITY OF ALCOHOLIC EXTRACT OF COSTUS PICTUS D. DON LEAVES IN WISTAR ALBINO RATS - KHOOSHBU, PASHA; ANSARI, IMTIYAZ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim was to assess the effect of anti-Alzheimer’s activity of the alcoholic extract of Costus pictus D. Don Leaves in Alzheimer induce Wistar albino rats. Methods: In the present study, the efficacy of an Extract of Costus pictus D. Don (ECPDD) was evaluated against scopolamine-induced Alzheimer in the Wistar albino rat. Donepezil at a dose of 2.5 mg/kg, ECPDD was given in rat at a dose of 100 mg/kg body weight, 150 mg/kg body weight, and 200 mg/kg body weight. Anti-Alzheimer activity was assessed by victimization novel object recognition test, elevated plus maze, and Y-maze. And by biochemical test like neurotransmitter esterase activity, catalase activity, malonyldialdehyd and glutathione assays. Results: Results showed that extracts treatment prevents Alzheimer and increases the level of acetylcholine, catalase, glutathione peroxidase, and phytochemical studies identified the presence of flavonoid and alkaloid in the ECPDD. Conclusion: According to the results, it was concluded that the leave of C. pictus D. Don has significant anti-Alzheimer activity due to the presence of potent antioxidants such as flavonoid and anticholinesterase enzyme present in alkaloids.